Miskonsepsi Pengerjaan Operasi Deret Aritmatika di PGMI 3 UIN Sumatera Utara - Namira Sazkia; Rora Rizki Wandini (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Misconceptions are concepts that are not relevant to scientific understanding accepted by experts in the field concerned and can cause difficulties in understanding material. The aim of this research is to examine the results of misconception analysis in working on arithmetic series operations at PGMI 3 UIN North Sumatra. This research uses survey and test methods to identify misconceptions that generally arise when PGMI-3 students work on arithmetic series operations. The research results show that there are several misconceptions involving understanding the general formula for arithmetic series, calculating the nth term, and adding terms in a series. Most of these misconceptions are related to inaccurate understanding and lack of focus on the basic concepts of arithmetic series. The type of error that many students make is an error in determining a formula with an error percentage of 20.49% and the error being made is an error in the final result determined, with an error percentage of 17.93%. Of the 39 students, there were 24 students who answered the questions correctly and well and there were 15 students who made different mistakes.